2009
DOI: 10.1111/j.1553-2712.2009.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Diversity in Emergency Medicine: Summary Recommendations from the 2008 Council of Emergency Medicine Residency Directors (CORD) Academic Assembly Diversity Workgroup

Abstract: Although the U.S. population continues to become more diverse, ethnic and racial health care disparities persist. The benefits of a diverse medical workforce have been well described, but the percentage of emergency medicine (EM) residents from underrepresented groups (URGs) is small and has not significantly increased over the past 10 years. The Council of Emergency Medicine Resident Directors (CORD) requested that a panel of CORD members review the current state of ethnic and racial diversity in EM training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…To address this knowledge gap, the Council of Emergency Medicine Residency Directors (CORD) requested that a panel of CORD members with expertise in workforce diversity and inclusion in medical education lead a workgroup on racial and ethnic diversity in EM as part of the best practices track during the 2008 CORD Academic Assembly. This panel of experts subsequently published a set of recommendations designed to augment physician diversity in EM (Table ) …”
Section: Summary Of Key 2008 Cord Recruitment Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this knowledge gap, the Council of Emergency Medicine Residency Directors (CORD) requested that a panel of CORD members with expertise in workforce diversity and inclusion in medical education lead a workgroup on racial and ethnic diversity in EM as part of the best practices track during the 2008 CORD Academic Assembly. This panel of experts subsequently published a set of recommendations designed to augment physician diversity in EM (Table ) …”
Section: Summary Of Key 2008 Cord Recruitment Recommendationsmentioning
confidence: 99%
“…Nevertheless, a recent study has shown that these best practices have not widely been adopted in EM with only 46% of program directors having implemented at least two strategies . Common reasons EM program directors cited for not implementing diversity recruitment strategies included a lack of resources, in terms of both money and time, and not believing that diversity was an organizational priority . While the health care landscape in the United States has changed dramatically during this time and the U.S. population has becoming increasingly diverse, diversity in EM has stagnated.…”
Section: Summary Of Key 2008 Cord Recruitment Recommendationsmentioning
confidence: 99%
“…In the USA, ethnic minorities (Hispanic, African‐American) currently comprise 27% of the population but will increase to 54% by 2050 . This has lead the American Society of Hospital Pharmacists, the College of Emergency Medicine and the American College of Physicians to develop recommendations designed to increase ethnic minority representation within their professions. In the publications, these organizations recognized the need to increase ethnic and minority representation, and acknowledge that within their respective fields, the rate of representation was low and had not increased appreciably in the previous decade.…”
Section: Developing An Indigenous Specialist Surgical Workforce In Aumentioning
confidence: 99%
“…Currently, there is little to no literature that addresses an organized approach to advancing URiM and LGBT faculty in EM . In 2008, a set of recommendations designed to augment physician diversity in EM was published by the 2008 Council of Emergency Medicine Residency Directors (CORD) Academic Assembly Diversity Workgroup; however, a follow‐up study suggested that these best practices have not been widely implemented …”
mentioning
confidence: 99%